STEAM education: Hearing the voices of the global south scholars - Castro-Romero, Oswaldo; Montaña Narváez, Emerson; Pelayo Pérez, Mariana Betzabeth; Orozco Salcedo, Abril Saknycte (American Journal of STEM Education, 2026)
This article presents a reflective dialogue on the special issue of the American Journal of STEM Education, which addresses STEAM education from a Global South perspective. This work challenges the traditional and technocratic views of education and proposes a more critical, inclusive, and interdisciplinary approach. It highlights the importance of empowering underrepresented communities, especially women and girls, through an education connected to the cultural and social realities of their territories. Likewise, the authors argue that STEAM education can become a form of resistance against new expressions of colonialism and inequality. The article emphasizes the need to strengthen public policies, teaching innovation, and academic collaboration in order to build fairer and more transformative educational models and bridges in response to contemporary challenges such as artificial intelligence, climate change, and technological inequalities.